Newly identified cerebral microbleeds in patients on anticoagulation for secondary stroke prevention - Šrámková, Tereza; Vaňásek, Tomáš; Šrámek, Martin; Janský, Petr; Benešová, Kateřina; Olšerová, Anna; Kmetonyová, Silvia; Paulasová-Schwabová, Jaroslava; Klíma, Michal; Michal, Lukáš; Kala, David; Otáhal, Jakub; et al. (Medicine (Baltimore), 2025)
Patients with cardioembolic ischemic stroke are commonly prescribed direct oral anticoagulants (DOACs), such as dabigatran (a direct thrombin inhibitor) and factor Xa inhibitors (e.g., apixaban and rivaroxaban), or warfarin to reduce the risk of recurrent stroke. A major concern in anticoagulant therapy is the risk of intracerebral hemorrhage, which is associated with a high mortality rate. Cerebral microbleeds (MBs), small asymptomatic brain hemorrhages detectable by susceptibility-weighted imaging (SWI) on magnetic resonance imaging (MRI), are associated with increased hemorrhagic stroke risk. This study evaluated the incidence of new MBs during 1 year of anticoagulation therapy in patients after cardioembolic stroke. Patients indicated for anticoagulant therapy after cardioembolic stroke and monitored in the cerebrovascular outpatient clinic of our department underwent brain MRI at baseline and after 1 year of therapy. The occurrence of new MBs was assessed using SWI sequences. MBs were categorized based on location into 3 groups: deep (dMBs), lobar (lMBs), and infratentorial (iMBs). A total of 79 patients were included, 53 of whom were male (67.1%), with a median age of 71 years (IQR: 64-76). The majority of patients (n = 50, 63.3%) were treated with apixaban, 16 patients (20.3%) with dabigatran, and 13 patients (16.5%) with warfarin. Baseline MRI revealed MBs in 17 patients (21.5%), including dMBs in 2, lMBs in 16, and iMBs in 2 patients. Follow-up MRI showed new MBs in 8 patients (10.1%), with new dMBs in 1, lMBs in 5, and iMBs in 4 patients. No statistically significant differences were observed in MBs the incidence of new MBs between anticoagulant groups (P = .912). Over 1 year of anticoagulant therapy, new MBs were detected in 10.1% of patients, predominantly in lobar and infratentorial regions. No differences in the incidence of new MBs were identified between the different anticoagulant groups.